Integrated care: mobilising professional identity. Issue 5 (17th August 2018) - Best, Stephanie; Williams, Sharon
Abstract : Purpose: Integrated care has been identified as essential to delivering the reforms required in health and social care across the UK and other healthcare systems. Given this suggests new ways of working for health and social care professionals, little research has considered how different professions manage and mobilise their professional identity (PI) whilst working in an integrated team. The paper aims to discuss these issues. Design/methodology/approach: A qualitative cross-sectional study was designed using eight focus groups with community-based health and social care practitioners from across Wales in the UK during 2017. Findings: Participants reported key factors influencing practice were communication, goal congruence and training. The key characteristics of PI for that enabled integrated working were open mindedness, professional trust, scope of practice and uniqueness. Blurring of boundaries was found to enable and hinder integrated working. Research limitations/implications: This research was conducted in the UK which limits the geographic coverage of the study. Nevertheless, the insight provided on PI and integrated teams is relevant to other healthcare systems. Practical implications: This study codifies for health and social care practitioners the enabling and inhibiting factors that influence PI when working in integrated teams. Originality/value: Recommendations in terms of how healthcare professionals manage and mobilise their PI when working in integrated teams are somewhat scarce. This paper identifies the key factors that influence PI which could impact the performance of integrated teams and ultimately, patient care.